2014
DOI: 10.5214/ans.0972.7531.210203
|View full text |Cite
|
Sign up to set email alerts
|

Performance of motor associated behavioural tests following chronic nicotine administration

Abstract: BackgroundNicotine has shown potential therapeutic value for neurodegenerative diseases though there are concerns that it may induce behavioural deficits.PurposeThe present study sought to determine the effect of chronic nicotine administration on overall motor functions and coordination.MethodsForty adult female and male Wistar rats were randomly grouped into 4 groups. Treated groups were administered nicotine via subcutaneous injections at doses of 0.25, 2 and 4 mg/kg body weight for 28 days. Control groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
1
6
2
1
Order By: Relevance
“…The loss in grip was also con rmed by the increased concentration of LDH and the neuronal degeneration which showed neurodegeneration in the experimental groups which was characterized by decreased population of Purkinje cells with Purkinje cells undergoing pyknosis and necrosis and loss of Cerebellar white mater. This disagrees with the previous study by Ijonome et al (35) which showed that nicotine produced no major de cit in the motor function and coordination as in animals of Group 2 with increased latency to grip and a slight reduction in the score on limb impairment. These suggest that the low doses of garlic and honey administered after nicotine administration had increased the latency to grip loss.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The loss in grip was also con rmed by the increased concentration of LDH and the neuronal degeneration which showed neurodegeneration in the experimental groups which was characterized by decreased population of Purkinje cells with Purkinje cells undergoing pyknosis and necrosis and loss of Cerebellar white mater. This disagrees with the previous study by Ijonome et al (35) which showed that nicotine produced no major de cit in the motor function and coordination as in animals of Group 2 with increased latency to grip and a slight reduction in the score on limb impairment. These suggest that the low doses of garlic and honey administered after nicotine administration had increased the latency to grip loss.…”
Section: Discussioncontrasting
confidence: 99%
“…Nicotine has been reported in previous studies to cause a reduction in body weight (35) and the result from the present study showed decrease in body weight in the treated groups compared to the Control which may be due to the reduction in food intake. This agrees with the previous studies of Ijomone et al (35); Omotoso and Babalola, (36). Our results also showed that there was increase in the body weight in Groups 7 and 8 compared to Group 2.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The locomotor and exploratory activities of the rats were recorded with the open-field test as described by Ijomone et al [13]. Narrow beam walking test was performed to assess the motor coordination requiring balance and equilibrium [14].…”
Section: Behavioural Assessment (Open Field Activity Narrow Beam Walmentioning
confidence: 99%
“…The apparatus used has been previously described [15]. Rats were placed singly in the centre of the OF, and the number of central squares (farther from walls) crossed, and peripheral squares (nearer to walls) that were crossed are noted for 5min.…”
Section: Open-fieldmentioning
confidence: 99%